2016
DOI: 10.1124/jpet.115.229971
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Monoacylglycerol Lipase Inhibitor MJN110 Produces Opioid-Sparing Effects in a Mouse Neuropathic Pain Model

Abstract: Serious clinical liabilities associated with the prescription of opiates for pain control include constipation, respiratory depression, pruritus, tolerance, abuse, and addiction. A recognized strategy to circumvent these side effects is to combine opioids with other antinociceptive agents. The combination of opiates with the primary active constituent of cannabis (D 9 -tetrahydrocannabinol) produces enhanced antinociceptive actions, suggesting that cannabinoid receptor agonists can be opioid sparing. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 89 publications
5
50
0
Order By: Relevance
“…In contrast, there are no reports in the literature testing whether inhibitors of endocannabinoid metabolizing enzymes are beneficial adjutants to opioid therapy in chronic pain patients. The results of the present study taken together with other studies that report individual inhibition of either FAAH or MAGL also produces opioid sparing antinociceptive effects with no added side effects (Miller et al, 2012; Wilkerson et al, 2016) supports the idea to initiate clinical trials to test whether FAAH, MAGL, or simultaneous FAAH and MAGL inhibition is opioid-sparing.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, there are no reports in the literature testing whether inhibitors of endocannabinoid metabolizing enzymes are beneficial adjutants to opioid therapy in chronic pain patients. The results of the present study taken together with other studies that report individual inhibition of either FAAH or MAGL also produces opioid sparing antinociceptive effects with no added side effects (Miller et al, 2012; Wilkerson et al, 2016) supports the idea to initiate clinical trials to test whether FAAH, MAGL, or simultaneous FAAH and MAGL inhibition is opioid-sparing.…”
Section: Discussionsupporting
confidence: 86%
“…These findings suggest that FAAH inhibition alone sufficiently augments morphine-induced antinociception and are consistent with the results of Miller et al (2012), who demonstrated that combination of the FAAH inhibitor URB597 and morphine produced additive antinociceptive effects in acetic acid-induced abdominal stretching and depression of wheel running in mice. In contrast combination of morphine and the MAGL inhibitor MJN110 produced synergistic antinociceptive effects in the CCI model (Wilkerson et al, 2016). Taken together, these results suggest that the endocannabinoid hydrolyzing enzyme inhibitors differentially interact with morphine in the CCI model of neuropathic pain, with FAAH inhibition producing additive antinociceptive effects and MAGL inhibition producing synergistic antinociceptive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this compound can be used in combination with morphine to produce synergistic analgesia and even appears to alleviate tolerance to opioid analgesia. A similar effect has also been noted using low-dose MAGL inhibition via MJN110 in combination with morphine in a rodent model of neuropathic pain (Wilkerson et al, 2016b). In our pain model, EM-2 in combination with URB597 enhanced antinociceptive activity, confirming the synergistic effects of ECs and opioids in pain suppression, being an exciting avenue for future research.…”
supporting
confidence: 84%
“…Interestingly, this compound can be used in combination with morphine to produce synergistic analgesia, and even appears to alleviate tolerance to opioid analgesia. A similar effect has also been noted using low dose MAGL inhibition via MJN110 in combination with morphine in a rodent model of neuropathic pain (Wilkerson et al, 2016b), suggesting this is an exciting avenue for future research.…”
Section: Blockade Of Ec Metabolism As An Analgesic Approach: Past supporting
confidence: 58%